2021
DOI: 10.1038/s41370-021-00390-w
|View full text |Cite
|
Sign up to set email alerts
|

Towards further harmonization of a glossary for exposure science—an ISES Europe statement

Abstract: The use of aligned exposure science terminology is crucial for ease of comparison and appropriate interpretation of exposure information, regulatory reports, and scientific publications. Sometimes the use of different terminology in different contexts and areas of exposure science results in diverging interpretations of the same descriptor. During the development of the European strategy for exposure science, the need was identified to agree on a defined terminology requiring an evaluation of the commonly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Through their collaborations, SRP teams identified that researchers should work together to standardize terminologies and improve and expand existing ontologies to keep pace with the evolution and complexity of research. For example, on the exposure science side, groups are working to develop aligned terminology to support comparison and interpretation of exposure information that can be used, among other things, to better inform the application of regulatory guidelines across continents . Similarly, a new collaborative initiative advancing community development and application of a harmonized language for describing research within EHS is underway. , …”
Section: What We Learned: Challenges and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through their collaborations, SRP teams identified that researchers should work together to standardize terminologies and improve and expand existing ontologies to keep pace with the evolution and complexity of research. For example, on the exposure science side, groups are working to develop aligned terminology to support comparison and interpretation of exposure information that can be used, among other things, to better inform the application of regulatory guidelines across continents . Similarly, a new collaborative initiative advancing community development and application of a harmonized language for describing research within EHS is underway. , …”
Section: What We Learned: Challenges and Recommendationsmentioning
confidence: 99%
“…For example, on the exposure science side, groups are working to develop aligned terminology to support comparison and interpretation of exposure information that can be used, among other things, to better inform the application of regulatory guidelines across continents. 48 Similarly, a new collaborative initiative advancing community development and application of a harmonized language for describing research within EHS is underway. 45,49 In parallel to ontologies, the knowledge graph is used to represent a collection of interlinked descriptions of entities that puts data in context while providing a framework for data integration, unification, analysis, and sharing.…”
Section: Recommendationsmentioning
confidence: 99%
“…• An exposure model (here "model") is a conceptual or mathematical representation of the exposure process [10,11]. As such it encompasses a concept, set of input parameters and mathematical equations that are defined based on a dataset or another source of past experience regarding exposure phenomena.…”
Section: General Approach and Processmentioning
confidence: 99%
“…Standard exposure scenario. In the context of exposure modelling, a standard exposure scenario is defined as "a combination of facts, assumptions, and inferences that define a discrete situation where potential exposures may occur…" [10,11]. Exposure estimates depend decisively on the scenario, and since an unlimited number of different scenarios is imaginable, some regulatory settings (e.g.…”
Section: General Approach and Processmentioning
confidence: 99%
“…Exposure science studies the contact between stressors and receptors and the associated exposure sources, exposure pathways, and processes potentially leading to impacts on human health and the natural and built environment. Stressors primarily refer to chemical, biological, and physical agents, and receptors range from molecules, cells, and organs to humans and other organisms [5]. Human exposure science is a critical component of the risk assessment process and is essential for establishing solid links in the environmental source-to-health outcome continuum and generating information that can be used to mitigate or prevent future adverse exposures [6, 7].…”
mentioning
confidence: 99%